Evaluation of the Tier 1 Program of Project P.A.T.H.S.: Secondary Data Analyses of Conclusions Drawn by the Program Implementers - Daniel T. L. Shek (The Scientific World Journal)
The Tier 1 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) is a curricula-based positive youth development program. In the experimental implementation phase, 52 schools participated in the program. Based on subjective outcome evaluation data collected from the program participants (Form A) and program implementers (Form B) in each school, the program implementers were invited to write down five conclusions based on an integration of the evaluation findings (N = 52). The conclusions stated in the 52 evaluation reports were further analyzed via secondary data analyses in this paper. Results showed that most of the conclusions concerning perceptions of the Tier 1 Program, instructors, and effectiveness of the programs were positive in nature. There were also conclusions reflecting the respondents’ appreciation of the program. Finally, responses on the difficulties encountered and suggestions for improvements were observed. In conjunction with the previous evaluation findings, the present study suggests that the Tier 1 Program was well received by the stakeholders and the program was beneficial to the development of the program participants.